Neotropical bats from Costa Rica harbour diverse coronaviruses - Moreira-Soto, A. (2015)
Bats are hosts of diverse coronaviruses (CoVs) known to potentially cross the host–species barrier. For analysing coronavirus diversity in a bat species-rich country, a total of 421 anal swabs/faecal samples from Costa Rican bats were screened for CoV RNA-dependent RNA polymerase (RdRp) gene sequences by a pancoronavirus PCR. Six families, 24 genera and 41 species of bats were analysed. The detection rate for CoV was 1%. Individuals (n = 4) from four different species of frugivorous (Artibeus jamaicensis, Carollia perspicillata and Carollia castanea) and nectivorous (Glossophaga soricina) bats were positive for coronavi- rus-derived nucleic acids. Analysis of 440 nt. RdRp sequences allocated all Costa Rican bat CoVs to the a-CoV group. Several CoVs sequences clustered near previously described CoVs from the same species of bat, but were phylogeneti- cally distant from the human CoV sequences identified to date, suggesting no recent spillover events. The Glossophaga soricina CoV sequence is sufficiently dis- similar (26% homology to the closest known bat CoVs) to represent a unique coronavirus not clustering near other CoVs found in the same bat species so far, implying an even higher CoV diversity than previously suspected.